Bad oscillations in Parkinson's disease. - Brown, P (2006)
Recordings in humans as a result of functional neurosurgery have revealed a tendency for basal ganglia neurons to oscillate and synchronise their activity, giving rise to a rhythmic population activity, manifest as oscillatory local field potentials. The most important activity is synchronised oscillation in the beta band (13-30 Hz), which has been picked up at various sites within the basal ganglia-cortical loop in PD. Dopaminergic medication and movement suppress this activity, with the timing and degree of suppression closely correlating with behavioural performance. Accordingly synchronisation in the beta band has been hypothesised to be essentially antikinetic in nature and pathophysiologically relevant to bradykinesia.